The Two-Level Game of Strategic Euroscepticism - Attewell, David N. (Tufts Archival Research Center, 2005)
At the heart of any federal polity lies a contestation of authority between the federal and state level. However, economist Gary Richardson made a key observation about the incongruous way in which this dynamic manifests itself in American budgetary politics. He found that even though red states are skeptical of government spending and federal authority in general, they are consistently net benefactors from the federal budget, while blue states are net contributors. Further investigation by journalists revealed that red state politicians were pursuing a strategy of federal-skepticism at both levels of the two-level game: attacking federal spending in the abstract, while courting it on the local level to maximize electoral advantage. I chose to examine the European Union to see if there was evidence, parallel with the US case, of strategic Euroscepticism associated with benefits from the EU budget. My thesis combined both quantitative and qualitative measures to test this relationship. Quantitatively, I tested correlations between measures of Euroscepticism in the member states and net receipts of EU spending. I also tested how the budgetary relationship of states to the EU changed when a Eurosceptic party entered or left government. The qualitative analyses were based on case studies of four countries which had experience of Eurosceptic parties in government: Italy, Austria, the UK, and Poland. These countries were the target of a more micro-level analysis, based on in-depth reading of both journalistic and political science literature, on how Eurosceptic rhetoric changed over time in each. The nature of these shifts was instructive in highlighting how political parties used Euroscepticism in domestic electoral competition, as well as in interstate bargaining. I found that the internal political-budgetary dynamics of the EU were similar to that of the U.S- strength of soft Eurosceptic representation in national parliaments was positively associated with net benefits from the EU budget. Quantitative and qualitative analyses suggested a model of strategic Euroscepticism on both echelons of the two-level game. Parties adopted or emphasized Eurosceptic rhetoric strategically in domestic electoral competition to differentiate themselves from traditionally Europhilic mainstream parties, and did the same at the supranational level in order to maximize leverage in interstate bargaining. Indeed, Soft Eurosceptic parties were in pole position to benefit from strategic Euroscepticism, as their problematization of specific policies gave them leverage in negotiations, but did not isolate themselves diplomatically as did extreme hard Eurosceptic parties. My thesis, thus sought to demonstrate the utility of a two-level games approach in evaluating Euroscepticism in the context of budgetary politics. It is a model of political and distributional contestation that can potentially be identified as an important feature of federal polities more generally.